ADAPTATION OF UKRAINIAN CORPORATE LEGISLATION TO EUROPEAN STANDARDS - Ivan Horodyskyy (Baltic Journal of Economic Studies, 2021)
Defining the European vector of development of Ukraine in the model of international cooperation as a priority involves the use of European standards in the field of law. This is impossible without careful adaptation work to bring the domestic legal system in line with the system that exists in the countries of the European Union. Recent changes in legislation have been long-awaited and have been a breakthrough in the corporate and financial sectors. The authors aim to carry out a comprehensive analysis of Ukrainian corporate law by comparing the political governance of Eastern Europe, economic and political aspects of the current situation, problems of corporate governance and ways to solve them, and the current stages of adaptation of corporate law in its transformation to the EU’s norms. In February 2018, the European Commission proposed to consider 2025 a possible date for the accession of Serbia and Montenegro, which means recognizing these countries as the first league in the Balkans, even in case the EU Council does not approve this date. The second league was set by the Council in June 2018, when 2019 was marked as a possible conditional date for the opening of accession negotiations with Albania and Macedonia. While the third league is for the accession of Bosnia and Kosovo, for which no date has been set. Negotiations with Turkey have been suspended. For comparison, if we take into account both political and economic indicators, Ukraine is approximately equal to the Balkan states of the second league. The prospect of EU membership has been recognized as the strongest external factor in domestic political change in the countries surrounding the EU. In accordance with the requirements of the Association Agreement with the EU on corporate law (EU Directives No. 2001/34/EC, No. 2003/71/EC, No. 2004/109/EC, No. 2007/14/EC, No. 2007/36/EC, No. 2012/30/ ЕС, No. 2013/34/ЕС, Recommendations of the European Commission No. 2005/162/ЕС and No. 2004/913/ЕС) the Law of Ukraine No. 2210-VIII, the Law of Ukraine “On Limited Liability and Additional Liability Companies” dated February 06, 2018 No. 2275-VIII, amendments to the Laws of Ukraine №514-VI, “On Securities and Stock Market”, “On Business Associations”, the Economic Code of Ukraine, the Civil Code of Ukraine, the Criminal Procedural Code of Ukraine and other laws were made and came into force on July 1, 2021 in the Law of Ukraine No. 738-IX. European integration transformation of Ukrainian legislation in the context of protection of shareholders’ rights was manifested through the implementation of Directive 2004/25/EC in the Law of Ukraine “On Amendments to Certain Legislative Acts of Ukraine Concerning the Simplification of Doing Business and Attracting Investments by Issuers of Securities” dated March 23, 2017 No. 1983-VIII and the Law of Ukraine No. 514-VI. Ukraine’s economy has not yet recovered from the negative effects of the global financial crisis of 2008, the political coup, the national crisis of 2015, the current crisis caused by the COVID-19 pandemic. This situation shows declining dynamics, and changes in Ukrainian legislation are offset, not showing real effect. The harmonization of Ukrainian legislation is complicated by the unwillingness of Ukraine’s business environment to comply with EU rules. Analyzing the activities of the JSC, the dynamics of the securities market, stock market and the transformation of Ukrainian legislation, the initiatives of certain branches of government, we can say that Ukraine is moving in the right direction but not fast enough and forms a country with a real market economy. Therefore, we can conclude that the adaptation of Ukrainian corporate law to EU legislation should be carried out not only in relation to existing EU directives but in accordance with general trends and prospects for the development of European corporate law.